2023
DOI: 10.30534/ijeter/2023/011122023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Premixed Flames with Ethanol Fuel affected Magnetic Field Induction

Abstract: The purpose of this study was to determine the effect of magnetic field induction on the characteristics of premixed ethanol combustion flames. Petroleum reserves will increasingly be depleted if alternative energy is not found. Therefore, various breakthroughs are needed to prevent an energy crisis from occurring. Simultaneously the researchers are also trying to find equipment that can save fuel consumption. To get a more effective and efficient flame, you can apply a magnetic field effect to the burning fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Research has indicated that magnetic field induction affects the characteristics of pre-mixed ethanol combustion flames, resulting in more effective and efficient flames [97]. Moreover, magnetization of bioethanol-gasoline fuel blends has been demonstrated to increase combustion energy in internal combustion engines, reduce emissions, and enhance combustion quality [98].…”
Section: Potential Applications Of Magnetic Field To Combustionmentioning
confidence: 99%
“…Research has indicated that magnetic field induction affects the characteristics of pre-mixed ethanol combustion flames, resulting in more effective and efficient flames [97]. Moreover, magnetization of bioethanol-gasoline fuel blends has been demonstrated to increase combustion energy in internal combustion engines, reduce emissions, and enhance combustion quality [98].…”
Section: Potential Applications Of Magnetic Field To Combustionmentioning
confidence: 99%